2013
DOI: 10.17795/ijep9359
|View full text |Cite
|
Sign up to set email alerts
|

Phytase Activity of Lactic Acid Bacteria Isolated from Dairy and Pharmaceutical Probiotic Products

Abstract: A B S T R A C TPhytate, the major storage form of phosphorus in plant seeds, can form insoluble complexes with minerals such as iron, zinc and calcium thus reducing their bioavailability. Phytase enzymes are often used to upgrade the nutritional quality of phytate-rich foods and feeds such as grains. The phytate-degrading activity of 43 lactic acid bacteria including isolates from commercial probiotic preparations, dairy products and type strains were measured. The phytate-degrading activity of bifidobacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…There was no intracellular phytase activity, whereas L. plantarum showed the highest extracellular phytase activity (6.3 mU/mL) (Zamudio et al, 2001). Khodaii et al (2013) reported that L. casei from dairy products exhibited higher phytase activity (> 0.004 U) than those isolates from pharmaceutical products (40% versus 27%) (Khodaii et al, 2013). Cizeikiene et al (2015) showed that the highest extracellular phytase activity produces Pediococcus pentosaceus strains from rye sourdough with 32 to 54 U/mL, respectively, under conditions similar to leavening of bread dough (Cizeikiene et al, 2015).…”
Section: Resultsmentioning
confidence: 97%
“…There was no intracellular phytase activity, whereas L. plantarum showed the highest extracellular phytase activity (6.3 mU/mL) (Zamudio et al, 2001). Khodaii et al (2013) reported that L. casei from dairy products exhibited higher phytase activity (> 0.004 U) than those isolates from pharmaceutical products (40% versus 27%) (Khodaii et al, 2013). Cizeikiene et al (2015) showed that the highest extracellular phytase activity produces Pediococcus pentosaceus strains from rye sourdough with 32 to 54 U/mL, respectively, under conditions similar to leavening of bread dough (Cizeikiene et al, 2015).…”
Section: Resultsmentioning
confidence: 97%
“…A 33-54% reduction was achieved by natural fermentation at 24 and by 72 h, 85% reduction was noted while in some samples the phytate could not be detected. On the contrary, only 18-32% reduction was achieved in LFP at 24 h and 37-49% reduction was achieved by 72 h. Bacillus subtilis (Shimizo 1992;Kerovuo et al 1998) andLAB species (Songr e-Ouattara et al 2008;Khodaii et al 2013) with phytase activities have been reported previously.…”
Section: Phytic Acidmentioning
confidence: 96%
“…[3]. Some microorganisms used in food fermentation such as S. cerevisiae, Schwanniomyces castellii [2], Lactic acid bacteria [23] and Bifdobacterium strains [24] have also been investigated for their phytase activity. For quantitative screening, the amount of released inorganic phosphate was determined in two different phytase-specific media and HS medium during bacterial cultivation.…”
Section: Qualitative and Quantitative Screening Of Phytate Degrading mentioning
confidence: 99%